Human Resource Transformation in Regional Development Management - Yantu, Irwan; Hinelo, Raflin (Journal of International Conference Proceedings, 2025)
This article discusses the transformation of human resources (HR) in the context of creative economy-based regional development in Indonesia. The shift towards creative economy-based management demands an increase in human resource competencies through relevant training and education. However, the main challenge faced is the skills gap of the workforce who still rely on conventional abilities. This study aims to analyze the HR transformation process, identify supporting and inhibiting factors, and measure the impact of transformation on regional development. A qualitative method with a case study approach was used to explore the experiences of stakeholders. The results show that collaboration between the government, private sector and educational institutions is crucial in creating an ecosystem that supports innovation and creativity. Successful HR transformation can improve regional competitiveness as well as create new jobs. This article provides strategic recommendations for stakeholders to accelerate the HR transformation process in the creative economy